Pengaruh Labelisasi Halal Terhadap Tingkat Penjual Produk ANH di Kecamatan Wangi-Wangi Kabupaten WAkatobi - Aisafah, Wa Ode Rani; Gurudin, Sitti Rahma (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2025)
This study aims to determine the effect of halal labeling on the sales level of ANH products in Wangi-Wangi District, Wakatobi Regency. This research employs a quantitative descriptive approach. Data were collected through questionnaires, observation, and documentation. The result show that halal labeling has a positive effect on the sales of ANH products. This indicates that the higher consumers’ awareness of halal labels, the higher the sales level of ANH peoductd. The findings also show that halal labeling serves as an important factor in purchasing decisions, especially among Muslim consumers, from the perspective of Islamic economics